Psychological Characterics of Expert Adaptation to Work Abroad - Туренко, Р.Л. (My University, 2016)
The article analysed the features|feature| of specialists adaptation|accomodation| to|by| them work|wrk| abroad. It is shown that adaptation|accomodation| of specialists to|by| the work|wrk| abroad is|appear| a tense|straighted| multipal process|Carbro| which|what| takes place during the whole time of work|wrk| abroad. There were found|exposes| out the personality features|feature| |individual| in specialists working abroad at different|diverse| time and cross-correlation relationship|definite| between personality|individual| descriptions of specialists regardless of time spent abroad.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; adaptation|accomodation|, personality|individual| of a specialist, work abroad.